Campaign Messages of Using Stainless-Steel Straws: A Theory of Planned Behavior Perspective - Kurniyawan, Dede (Mediator: Jurnal Komunikasi, 2023)
Tackling climate change is the 13th goal in the Sustainable Development Goals (SDGs). One of the simple actions that can be taken to prevent the issue of climate change is the use of environmentally friendly straws, specifically the use of stainless-steel straws. For the public to know about the issue of climate change, social media has an important role. This study aims to see the effect of the exposure of messages on social media related to climate change issues on the behavior to use stainless-steel straws. In addition, this study uses predictors of the Theory of Planned Behavior, namely attitudes, subjective norms, and Perceived Behavioral Control (PBC). Using Structural Equation Modeling (SEM), the study results show that attitudes, subjective norms, and Perceived Behavioral Control (PBC) directly influence intentions and indirectly influence the behavior of using stainless-steel straws. Another finding is that exposure to persuasive messages on social media related to the use of environmentally friendly straws owned by family and close friends also has a direct positive effect on attitudes, subjective norms, Perceived Behavioral Control, and behavioral intentions, which in turn have a positive indirect effect on the behavior of using stainless-steel straws.